Laboratorio de Trigonometría - Cordero-Quirós, Marcial (My University, 2020)
Infografía donde se muestra el contenido matemático denominado Ley de Senos, su definición y ejemplos. Además se presenta un pequeño laboratorio para demostrar la utilidad del concepto matemático.

Infographic showing the mathematical content called Law of Sines, its definition and examples. A small laboratory is also presented to demonstrate the usefulness of the mathematical concept.
Keywords: Trigonometría; Ley de Senos; Didáctica; Matemáticas; Trigonometry; Didactics; Mathematics